Particle‐Assisted Optoelectronic Tweezers for Manipulating Single Cells and Microparticles - Ao Wang; Shuzhang Liang; Caiding Ni; Yongyi Jia; Kangjie Wu; Wenyan Niu; Shunxiao Huang; Kaiyi Peng; Chutian Wang; Yingjian Guo; Zhijun Zhao; Lingze Zhang; et al. (Advanced Science)
Abstract Manipulation of single cells or particles is crucial in the biomedical field. However, precisely and rapidly manipulating single cells without damaging them is a significant challenge. In this study, a novel strategy for indirect manipulation of cells and microparticles that can satisfy these requirements via a combination of particle‐induced dielectrophoretic forces (PiDEP) and optoelectronic tweezers (OET) is developed. This strategy is based primarily on the principle that particles experiencing the same dielectrophoretic forces tend to repel each other, whereas those experiencing different forces are attracted to each other. During the manipulation, Ag‐SiO2 microparticles controlled by the OET act as intermediaries for manipulating other particles or cells through dielectrophoretic forces. Thus, the manipulation range of the OET can be expanded by two to three times its original size, and the manipulation speed can be significantly increased while maintaining its precision. Furthermore, the results indicate that the proposed method can effectively reduce cell damage to one‐third of that caused by traditional OET. This study demonstrates the significant potential of particle‐assisted OET for single‐cell manipulation and offers an effective strategy for manipulating cells and microparticles.